Risk Aversion and the Intertemporal Behavior of Asset Prices - Stapleton, R. C.; Subrahmanyam, M. G. (Review of Financial Studies, 1990)
In this article, we characterize economies in which both cash flows and forward prices follow random walks. We show in the case of geometric random walks that the preferences of the representative investor are of the constant proportional risk-aversion type. We also show the conditions under which spot prices follow random walks and under which the equivalent martingale measure is non-state-dependent.